SWOT Analysis and Consumer Purchase Intention CloudThink Fashion Business - Khariful Syukri; Indah Sari Rahmaini (Universitas Negeri Padang, 2025)
This article aims to examine SWOT analysis and consumer purchasing decisions in CloudThink Fashion Business. This paper uses quantitative research methods with a descriptive type and a literature review. Studies show that SWOT analysis and consumer purchasing decisions are fundamental disciplines in marketing and business strategy, exploring various factors that influence individual purchasing decisions, preferences, and interactions with products or services. The interaction between cognitive, affective, and conative processes creates a nuanced understanding of consumer purchasing intentions.